18F-FDG-PET/CT of peritoneal tumors: a pictorial essay. Issue 1 (January 2017) - Dubreuil, Julien; Giammarile, Francesco; Rousset, Pascal; Rubello, Domenico; Colletti, Patrick M.; Glehen, Olivier; Skanjeti, Andrea
Abstract : Cancer imaging on the peritoneum is quite difficult on PET/CT because of the particular anatomical features of this membrane. The abdominal cavity can be the seat of very different primary or secondary tumoral lesions, with heterogeneous aggressiveness and variable fluorine-18 fluorodeoxyglucose uptake and patterns. We aimed to depict a spectrum of appearances with abnormal fluorine-18 fluorodeoxyglucose uptakes localized on the peritoneum in frequent conditions such as peritoneal carcinomatosis and in rarer disease such as desmoplastic round cell tumor.